2000
DOI: 10.1007/s005950070004
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Metastasis-Related Carbohydrate Epitopes of Gastric Cancer with Submucosal Invasion

Abstract: This study was conducted to examine the lymph node metastasis-related carbohydrate epitopes of cancer cells in primary lesions of gastric cancer with submucosal invasion (sm gastric cancer). A total of 118 formalin-fixed and paraffin-embedded surgical specimens were studied. Carbohydrate epitopes were detected histochemically using 17 kinds of biotin-labeled lectins and three kinds of monoclonal antibodies (mAbs) against Thomsen-Friedenreich antigen (HB-T1), Tn (HB-Tn1), and sialyl Tn antigens (HB-STn1). The n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…STn expression is broadly reported to be correlated with invasiveness of many epithelial cancers [13][14][15][16], including breast cancers [18,35]. However, it has been also reported that STn reactivity of distant metastases is lower than in their respective primary ovarian tumors [36].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…STn expression is broadly reported to be correlated with invasiveness of many epithelial cancers [13][14][15][16], including breast cancers [18,35]. However, it has been also reported that STn reactivity of distant metastases is lower than in their respective primary ovarian tumors [36].…”
Section: Discussionmentioning
confidence: 97%
“…Correlation between STn expression and lymph node involvement or distant metastasis, is usually observed in gastric [13][14][15], colorectal [16] and breast cancers [17,18]. It has been also reported that STn expression is enhanced in the invasive front of ovarian tumors compared to deeper location in the tumor mass [19].…”
Section: Introductionmentioning
confidence: 98%
“…In gastric cancers, numerous studies reported a positive association of STn expression (in serum or primary tumors) with lymph node metastasis [25,73,75,88,89,93], peritoneal metastasis [25,73,77,88] and liver metastasis [73,88] with few contradicting reports [65]. Logically, many authors also reported a correlation between STn expression and decreased survival [26,65,72,75,88,94].…”
Section: Stn Immunodetection In Tissues and Tumorsmentioning
confidence: 99%
“…This observation indicates that the distribution and expression of glyconjugates in the surface were altered (40) . The Con A, LTA and PNA lectins were useful and distinguished among benign and malignant epidermal neoplasms.…”
Section: Image Analysis Data Of Lectin Histochemistry In the Areamentioning
confidence: 89%
“…In neoplasic cells the increase on the content and/or expression of surface carbohydrates have been documented using lectin histochemistry (14,40) . Lectins are sensible, stable and easy-touse tools to differentiate transformed and non-transformed cells (4,9,24,37) .…”
Section: Discussionmentioning
confidence: 99%